Pelatihan Pemantauan Pertumbuhan Balita Pada Kader Kesehatan di Puskesmas Muara Tais, Kecamatan Angkola, Muara Tais Tapanuli Selatan - Irwan Batubara; Sri Juwarni; Herawati Harahap (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Stunting in Tapanuli Selah district will be 39.4 percent in 2022, and in 2023 it will decrease by 15.6 percent. Community empowerment in the health sector develops Community Resource Health Efforts (UKBM) namely Posyandu. Posyandu organizers are health cadres, elected by the community. Increasing the ability of cadres to manage posyandu activities, especially regarding basic health services to the community, is carried out by training by health workers. Muaratais Health Center was inaugurated on July 15 2023, the newest sub-district expansion in South Tapanuli Regency. The Muaratais Health Center area has 15 villages, in each village there is a posyandu, an average of 4 cadres and there are new cadres who have never attended training. The service team agreed with the Community Health Center to carry out training for posyandu cadres on monitoring the growth of toddlers. Training materials, toddler growth, measuring body length, height and weight using tools available at the posyandu, infant ruler, microtoise, portable electric body weight. The training participants consisted of 20 health cadres, appointed by the community health center to represent the posyandu in their work area. Training activities were carried out for two days in the community health center meeting room. Lecture, question and answer, simulation and demonstration methods. Trainees' knowledge about monitoring toddler growth is getting better. Skills in using the growth monitoring tools available at posyandu category are sufficient. Skills at the advanced stage are continued by the posyandu supervisor.